2016
DOI: 10.1111/bju.13445
|View full text |Cite
|
Sign up to set email alerts
|

Technical mentorship during robot‐assisted surgery: a cognitive analysis

Abstract: This study objectively evaluated the cognitive engagement of a surgical mentor teaching technical skills during surgery. The study provides a deeper understanding of how surgical teaching actually works and opens new horizons for assessment and teaching of surgery. Further research is needed to study the feasibility of this novel concept in assessment and guidance of surgical performance.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 27 publications
(19 citation statements)
references
References 30 publications
0
18
1
Order By: Relevance
“…Communication in RAS is challenging because of the congestion of equipment and the altered operating theatre dynamics, with isolation of the surgeon on the console away from the patient and the bedside assistants [4,5,7,26]. The Agency for Healthcare Research and Quality recommended against the use of non-verbal communication because of its Acknowledgement P = 0.02 Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Communication in RAS is challenging because of the congestion of equipment and the altered operating theatre dynamics, with isolation of the surgeon on the console away from the patient and the bedside assistants [4,5,7,26]. The Agency for Healthcare Research and Quality recommended against the use of non-verbal communication because of its Acknowledgement P = 0.02 Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Results showed that performance level decreased (FSRS metrics increased) by increase of difficulty level. Our previous studies showed that NASA-TLX scores given by trainee are not reliable for expertise level assessment as we could not find any significant correlation between individual NASA-TLX metrics and expertise level (assessed by expert RAS surgeons) [ 20 , 29 ], maybe because trainee doesn’t have enough proficiency to consider all necessary factors in evaluation [ 6 , 20 , 29 ].…”
Section: Resultsmentioning
confidence: 98%
“…The results in Table 4 may suggest that although scores given to individual NASA-TLX are not reliable for expertise level assessment [ 6 , 20 , 29 ], difficulty level feature (calculated by using some of these metrics) can be an informative feature toward performance evaluation during RAS skill acquisition.…”
Section: Resultsmentioning
confidence: 99%
“…EEG signals were also used to identify cognition patterns of a surgical mentor and trainee when teaching RAS skills. It was found that the mentor's workload increased when the trainee's workload decreased [8].…”
Section: Sensor-based Workload Assessmentmentioning
confidence: 99%
“…Some potential of assistive strategies that will be enabled with cognitive load sensing include using virtual fixtures to prevent risky motions [2], removing unintentional hand tremors [3], taking over simple and repetitive subtasks [4], and providing augmented reality cues about future steps [5]. Providing intraoperative workload feedback would also accelerate surgeon training programs [6,7] by customizing training according to individual stress profiles and focusing on the specific task demands that are associated with high cognitive load [8].…”
Section: Introductionmentioning
confidence: 99%